Manajemen Pendidikan Agama Islam di Masjid berbasis Layanan Umat - Khaerul Anwar; Choeroni Choeroni; Mumtaz Fatimah az-Zahro (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
The rapid growth of mosques in Indonesia is a matter of pride for us Muslims. But it's really unfortunate, it turns out that the existence of hundreds of thousands of mosques in general are still only functioning as "mahdlah" places of worship. In fact, if we go back to the history of the mosque at the time of Rasulullah Muhammad Sallahu Alaihi Wasallam, then the existence of the mosque has multiple functions whose beneficial effects are felt for the people. The purpose of this study is to elaborate on the practice of congregational service-based mosque management which has been successfully practiced at the Al-Falah mosque in Sragen which is viral because of its unique management. The target that researchers want to obtain through this research is to obtain a clear picture of congregational service-based mosque management. The method in this study is to use a qualitative descriptive method by going directly to the research site. The results of the study prove that the Al-Falah mosque in Sragen has unique management and is based on community services, including services in Islamic Religious Education (PAI) activities.